POLITICAL MARKETING PARTAI POLITIK DALAM PEMILIHAN UMUM PRESIDEN TAHUN 2009 (Studi Pada Dewan Pimpinan Daerah Partai Demokrat Provinsi Sumatera Utara) - Pohan, Zafar Siddik (Universitas Medan Area, 2014)
Political marketing is the method and application of marketing concepts in a political context. Political marketing is seen as a set of methods that can facilitate the contestant (individual or political party) political initiatives in marketing, political ideas, political issues, political ideology, and the characteristics of party leaders and the party's work program to the public or the contestants. So therefore yan political marketing is done by the Democratic party (Democratic Party Regional Leadership Council of North Sumatra Province) is how to market their products in the context of political marketing political constituency or community so that in fact the Democrats can win a pair Susilo Bambang Yudhoyono at the Presidential election and Vice President in 2009 and then in one round.In this research, a description of research methods, namely by using in-depth interviews and literature to ekplorasikan about political marketing political parties in the 2009 presidential elections in the North Sumatra Regional Leadership Council of the Democratic Party of North Sumatra Province.